Meningkatkan Kekuatan Tarik Bambu Melalui Durasi Pengawetan Bambu - Noverma Noverma; Oktavi Elok Hapsari; Yusrianti Yusrianti; Tira Roesdiana (Universitas Kristen Maranatha, 2026)
Bamboo is a potential alternative material to replace wood and steel, offering several advantages such as favorable physical and mechanical properties, lightweight characteristics, high moisture tolerance, elasticity, and a significantly shorter growth cycle compared to wood. However, bamboo also has notable disadvantages, including low natural durability and vulnerability to powder-post beetle attacks. To address these issues, preservation treatments are recommended prior to use, although the type and duration of treatment may influence the physical and mechanical properties of bamboo, thereby affecting its quality. This study aims to determine the optimal treatment duration to enhance the tensile strength of bamboo through a simple and environmentally friendly preservation method, namely immersion in either freshwater or saltwater for varying durations (1 × 24 hours, 3 × 24 hours, and 14 × 24 hours), followed by tensile strength testing. The results indicated that the highest tensile strength was obtained with a treatment duration of 3 × 24 hours, with treated specimens exhibiting an increase in tensile strength ranging from approximately 10% to 30% compared to untreated samples. Furthermore, bamboo treated with saltwater demonstrated higher tensile strength than that treated with freshwater, suggesting that both treatment duration and type of preservative significantly affect tensile performance. It can be concluded that inappropriate treatment durations—either too short or too long—may lead to suboptimal tensile strength in bamboo.